A combined experimental/numerical study on the scaling of impact strength and toughness in composite laminates for ballistic applications. (15th August 2020) - Signetti, Stefano; Bosia, Federico; Ryu, Seunghwa; Pugno, Nicola M.
Abstract: In this paper, the impact behaviour of composite laminates is investigated, and their potential for ballistic protection assessed, as a function of the reinforcing materials and structures for three representative fibre-reinforced epoxy systems involving carbon, glass, or para-aramid fibre reinforcements, respectively. A multiscale coupled experimental/numerical study on the composite material properties is performed, starting from single fibre, to fibre bundles (yarns), to single composite ply, and finally at laminate level. Uniaxial tensile tests on single fibres and fibre bundles are performed, and the results are used as input for non-linear Finite Element Method (FEM) models for tensile and impact simulation on the composite laminates. Mechanical properties and energy dissipation of the single ply and multilayer laminates under quasi-static loading are preliminarily assessed starting from the mechanical properties of the constituents and subsequently verified numerically. FEM simulations of ballistic impact on multilayer armours are then performed, assessing the three different composites, showing good agreement with experimental tests in terms of impact energy absorption capabilities and deformation/failure behaviour. As result, a generalized multiscale version of the well-known Cuniff criterion is provided as a scaling law, which allows to assess the ballistic performance of laminated composites, starting from the tensile mechanical properties of the fibres and fibre bundles and their volume fraction. The presented multiscale coupled experimental-numerical characterization confirms the reliability of the predictions for full-scale laminate properties starting from the individual constituents at the single fibre scale.